Culture as Contradiction in Urban Regeneration: Sanitization, Commodification, and Critical Resistance in Liverpool One - Malone, Niamh (Archīum Ateneo, 2024)
This essay uses critiques of the homogenization of urban regeneration practices over recent decades to examine Liverpool ONE (L1), a privately owned, open-air retail development in the center of the historic city. The argument considers the role of a particular concept of culture in enabling major projects, which frequently involve the conversion of public resources into private assets, to be projected in a benign light. Countering this trend is a core mission for New York-based activist artist, Reverend Billy and his Church of Stop Shopping Choir; an inspiration to young artists in Liverpool. Since opening, L1 has functioned as a focal point for critical cultural interventions, whereby artists draw attention to the enclosure of urban democracy that results from the corporate takeover of established commercial streets. This essay examines two interventionist projects which deployed the potential of performance to critique Liverpool ONE: Duke Aid, executed by undergraduate performing arts students from Liverpool Hope University (2009), and Ghost Town (Liverpool Gothic Festival, 2013), written and performed by Alice Colquhoun and Izzy Major.